UJI EFEKTIFITAS DAYA ANTHELMINTIK EKSTRAK KULIT BATANG LENGARU (Alstonia scholaris R.Br) SECARA IN VITRO - Muhajir Lamasai; Ramadhanil Ramadhanil; Syariful Anam (Biology Department, Mathematics and natural science, Tadulako University, 2015)
The study entitled “Anthelmintic Effectiveness Test of Lengaru Bark Extract (Alstonia scholaris R.Br) by In Vitro method was done during September to December 2014. The purpose of this research was to determine the effectiveness of anthelmintic lengaru bark extract (A. scholaris R.Br.) by in vitro methode. This research was an experimental laboratory research and designed by Completed Random and Design with 11 (eleven) threatments and 3 (three) replications and probit analysis was used for data analysis. The sample extracted used reflux method and this research.Ascaris lumbricoides was taken from pig intestine from Slaugterhouse in Bali Street, South Palu. The result of the research was indicated that lengaru extract has anthelmintic potency with LC50 as high as 16.61% and 72.80 minutes for LT50.Keywords : Bark ekstract lengaru (A. scholaris R.Br.), A. lumbricoides, Anthelmintic.